Symmetry and Symmetry-Breaking in Semiconductors Fine Structure of Exciton States - Hönerlage, Bernd (Springer Tracts in Modern Physics, 2018)
This book discusses group theory investigations of zincblende and wurtzite semiconductors under symmetry-breaking conditions. The text presents the group theory elements required to develop a multitude of symmetry-breaking problems, giving scientists a fast track to bypass the need for recalculating electronic states. The text is not only a valuable resource for speeding up calculations but also illustrates the construction of effective Hamiltonians for a chosen set of electronic states in crystalline semiconductors. Since Hamiltonians have to be invariant under the transformations of the point group, the crystal symmetry determines the multiplet structure of these states in the presence of spin-orbit, crystal-field, or exchange interactions. Symmetry-breaking leads to additional coupling of the states, resulting in shifts and/or splittings of the multiplets. Such interactions may be intrinsic, as in the case of the quasi-particle dispersion, or extrinsic, induced by magnetic, electric, or strain fields. Using a power expansion of the perturbations these interaction terms can be determined in their parameterized form in a unique way. The hierarchic structure of this invariant development allows to estimate the importance of particular symmetry-breaking effects in the Hamiltonian. A number of selected experimental curves are included to illustrate the symmetry-based discussions, which are especially important in optical spectroscopy. This text is written for graduate students and researchers who want to understand and simulate experimental findings reflecting the fine structure of electronic or excitonic states in crystalline semiconductors. .